2021
DOI: 10.1038/s41598-021-85359-3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcomes of COVID-19 in HIV-infected individuals: a systematic review and meta-analysis

Abstract: Susceptibility to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and the risk of mortality among people living with human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) (PLWHA) is largely unknown. PLWHA are unique due to their altered immune system from their history of chronic HIV infection and their use of antiretroviral therapy, some of which have been used experimentally to treat coronavirus disease 2019 (COVID-19). Therefore, we conducted a systematic review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
250
5
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 253 publications
(285 citation statements)
references
References 41 publications
21
250
5
9
Order By: Relevance
“…Research ndings on these concerns have been in agreement with previous studies conducted elsewhere [18,19,[33][34][35][36]. Studies indicated that though the pandemic affected the health care for all disease conditions, chronic patients such as people living with HIV are likely to be uniquely vulnerable [4,37,38]. In our ndings, those who had formal education are more likely to have care and treatment services.…”
Section: Discussionsupporting
confidence: 90%
“…Research ndings on these concerns have been in agreement with previous studies conducted elsewhere [18,19,[33][34][35][36]. Studies indicated that though the pandemic affected the health care for all disease conditions, chronic patients such as people living with HIV are likely to be uniquely vulnerable [4,37,38]. In our ndings, those who had formal education are more likely to have care and treatment services.…”
Section: Discussionsupporting
confidence: 90%
“…Most of the 21 studies were excluded because they had no non-HIV comparison group (n= 16), three were excluded because they did not report on the outcomes of this review (31)(32)(33), and one study was a duplicate (34). One study (19) used population-based totals and did not report totals with confirmed COVID-19 infection and was therefore excluded. A total of 11 studies were finally included.…”
Section: Search Resultsmentioning
confidence: 99%
“…It could also due to HIV being more prevalent in people less than 55 years ( Himwaze et al, 2020 ). HIV may also play a role since it is considered a risk factor for acquiring SARS-CoV-2 infection and is associated with a higher risk of mortality from COVID-19 ( Ssentongo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%